2012
DOI: 10.1007/s00276-012-0977-0
|View full text |Cite
|
Sign up to set email alerts
|

Double innervation of the brachialis muscle: anatomic–physiological study

Abstract: Variations in the relative percentage of innervation from the radial nerve could be due to the different sizes and shapes of this branch. The functional significance of this branch can become crucial if the main innervation to the brachialis muscle fails. When planning surgical antero-external approach to the humerus, it should be kept in mind and preserved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
2
6
0
Order By: Relevance
“…SILVA, D. L.; BARBOSA, F. T.; RODRIGUES, A. K. B. F.; RAMOS, F. W. S.; DE LIMA, F. C.; GALVAO, A. M. N; LIRA, F The results of this study in all cases of branching described, the innervation of brachialis and coracobrachialis muscles by the musculocutaneous nerve, reinforces what the previous studies related to these muscles stated, recognizing that all the anterior compartment of the arm present innervation from this nerve (Spinner et al;Blackburn et al;Frazer et al;Leonello & Bain;Dang & Rodner, 2009;Bendersky & Bianchi) as well as in classic anatomy textbooks (Gérard, 1912;Hollinshead, 1966;Prives et al;Woodburne, 1984;Benninghoff & Goerttler;van de Graaff;García-Porrero & Hurlé, 2005).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…SILVA, D. L.; BARBOSA, F. T.; RODRIGUES, A. K. B. F.; RAMOS, F. W. S.; DE LIMA, F. C.; GALVAO, A. M. N; LIRA, F The results of this study in all cases of branching described, the innervation of brachialis and coracobrachialis muscles by the musculocutaneous nerve, reinforces what the previous studies related to these muscles stated, recognizing that all the anterior compartment of the arm present innervation from this nerve (Spinner et al;Blackburn et al;Frazer et al;Leonello & Bain;Dang & Rodner, 2009;Bendersky & Bianchi) as well as in classic anatomy textbooks (Gérard, 1912;Hollinshead, 1966;Prives et al;Woodburne, 1984;Benninghoff & Goerttler;van de Graaff;García-Porrero & Hurlé, 2005).…”
Section: Discussionsupporting
confidence: 87%
“…Some texts and researches have been reporting a dual innervation of brachialis muscle, from musculocutaneous and radial nerves (Leonello et al, 2007;Bendersky & Bianchi, 2012), being the inferolateral segment the part that receives the biggest supply of radial nerve (Spinner et al, 2003). Some authors allege that the importance of these contributions from radial nerve is not known (Frazer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, many researchers disagree. Bendersky and Bianchi (2012) analyzed the double innervation and components of the two nerves using electrophysiology methods. That study observed double innervation 90% of the time, and the radial nerve were reported to serve as a motor branch.…”
Section: Discussionmentioning
confidence: 99%
“…Frazer et al () found that the distribution of the radial nerve overlaps with that of the MCN within the brachialis muscle. Moreover, one study found that patients with radial nerve paralysis presented with denervation on MRI scans, further supporting the distribution of the radial nerve on the brachialis muscle (Bendersky and Bianchi, ). This variation in findings regarding the innervation of the brachialis muscle is thought to stem from differences in race, number of samples, and research methods between studies.…”
Section: Introductionmentioning
confidence: 99%
“…The larger, superficial head originates from the anterolateral aspect of the middle third of the humerus and the lateral intermuscular septum, whereas the smaller, deep head originates from the distal third of the anterior aspect of the humerus and the medial intermuscular septum. Moreover, it has been stated that the brachialis muscle has a double innervation: the main innervation of the brachialis muscle by the musculocutaneous nerve and additional branches from the radial nerve [4][5][6][7]. To the best of our knowledge, there are no reports assessing whether ultrasound and MRI are able to demonstrate the two heads of distal brachialis attachment in vivo.…”
mentioning
confidence: 99%